Bioactive polyketide derivatives from the endophytic fungus Phaeosphaeriopsis musa. (March 2022) - Zhong, Jinqian; Chen, Yuchan; Liu, Zhaoming; Hu, Caiyun; Li, Saini; Liu, Hongxin; Zhang, Weimin
Abstract: Two undescribed phenolic derivatives musaones A and B, six undescribed γ -butyrolactone musaolides A-F, together with two undescribed cyclopentanone musaolides G and H were isolated from the solid culture of an endophytic strain Phaeosphaeriopsis musae M. Arzanlou & Crous (Phaeosphaeriaceae) . Their structures were unambiguously elucidated by extensive spectral analyses. The absolute configurations of two diastereomers musaolides G and H were assigned by comparing their experimental and calculated ECD data. Moreover, the in vitro α -glucosidase inhibition and cytotoxic activities of isolated compounds (except musaolide D) were evaluated to understand their biological effects, wherein musaone B and musaolide F displayed promising α -glucosidase inhibition with IC50 values of 37.3 ± 0.59 μM and 105.18 ± 2.76 μM respectively, compared to the positive control acarbose (24.99 ± 1.28 μM). Graphical abstract: Two new phenolic derivatives musaones A and B, six new γ -butyrolactone musaolides A-F, together with two new cyclopentanones musaolides G and H were isolated from the solid culture of an endophytic strain Phaeosphaeriopsis musae A727 . Image 1 Highlights: Musaones A and B were isolated from Phaeosphaeriopsis musae A727. Musaolides A-F were isolated from Phaeosphaeriopsis musae A727. Musaolides G and H were isolated from Phaeosphaeriopsis musae A727. Musaone B and musaolide F displayed moderate α -glucosidase inhibition activity.